Gadolinium-doped cerium oxide nanorods: novel active catalysts for ethanol reforming - Godinho, Mario; Goncalves, Rosana de F.; Leite, Edson R.; Raubach, Cristiane W.; Carreno, Neftali L. V.; Probst, Luiz F. D.; Longo, Elson [UNESP]; Fajardo, Humberto V. (Springer, 2010)
The gadolinium-doped ceria nanorods (Gd(0.2)Ce(0.8)O(2-x) ) were synthesized by hydrothermal treatment. It was shown that the use of microwave heating during hydrothermal treatment decreases the treatment time required to obtain gadolinium-doped ceria nanorods and that oriented attachment is the dominant mechanism responsible for anisotropic growth. It was clear that Gd(0.2)Ce(0.8)O(2-x) nanorods were more catalytically active than commercial CeO(2) in the ethanol reforming reaction.